COVID-19 and molecular mimicry: The Columbus' egg?. (July 2020) - Cappello, Francesco
Highlights: Recently, this Journal published a report about Guillain-Barré syndrome associated with COVID-19 infection. Guillain-Barré syndrome can be due to molecular mimicry phenomena. Molecular mimicry had already been described in another SARS. It could explain the autoimmune signs and symptoms that some patients affected by SARS-CoV-2 can experience.